(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This hierarchicalvision of social diversity draws on what Sleeter and Grant (1988) call a"deficiency orientation." Problems exist for those who are"different" from the norm–for limited English speakers, students ofcolor, and so on. Learners were seen as varying in the degree to which theydiffered from the norm. Respondents often described in apparently sympathetictones the" victims" of difference, their need for self-esteem, and areaffirmation of their "right" to education.